2006
DOI: 10.1542/peds.2005-2854
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Television, Movie, and Video Game Exposure and School Performance

Abstract: We found that both content exposure and screen time had independent detrimental associations with school performance. These findings support parental enforcement of American Academy of Pediatrics guidelines for media time (particularly weekdays) and content limits to enhance school success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
3
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 29 publications
7
117
3
9
Order By: Relevance
“…It consequently has a negative image. Also, actual television viewing is thought to take up time that could otherwise be spent on school-related activities and thus provides little cognitive competency (Hancox et al, 2005;Sharif & Sargent, 2006;Verboord & Van Rees, 2003). Spending large amounts of time watching television would therefore poorly match with school culture and curricula, especially at higher levels of education.…”
Section: Socialization By Parental Media Examplementioning
confidence: 99%
See 1 more Smart Citation
“…It consequently has a negative image. Also, actual television viewing is thought to take up time that could otherwise be spent on school-related activities and thus provides little cognitive competency (Hancox et al, 2005;Sharif & Sargent, 2006;Verboord & Van Rees, 2003). Spending large amounts of time watching television would therefore poorly match with school culture and curricula, especially at higher levels of education.…”
Section: Socialization By Parental Media Examplementioning
confidence: 99%
“…Some studies however report positive effects of cer-tain TV behavior on children's cognitive and linguistic skills (Gentzkow & Shapiro, 2006;Wright et al, 2001). Parents are generally presumed to play a decisive role in teaching children how to deal with television's attractions (Sharif & Sargent, 2006). Parents provide an example by way of their own television viewing behavior, and they also guide their children's television viewing, for instance, by giving instructions or by coviewing.…”
Section: Introductionmentioning
confidence: 99%
“…Late night interactive gaming can also causes similar delays in sleep onset and daytime difficulties. Exposure to violent video games and movies also have the added risk of increasing physiological arousal, aggression-related thoughts and feelings, aggressive behavior, as well as decreasing overall prosocial behavior and academic performance (Anderson, & Bushman, 2001;Sharif, & Sargent, 2006). As such, a "turn in" policy will help parents to control unmonitored use at night.…”
Section: The Importance Of Monitoring Technology Use In the Homementioning
confidence: 99%
“…Likewise at their individual homes, they invest extraordinary arrangement of energy in person to person communication exercises leaving their investigations to a discouraging state which may have unfavorable impact on their scholastic exhibitions. Concentrates from literary works demonstrate that person to person communication media has increased impressive consideration as a factor influencing student' scholarly execution While there are distributed literary works on the impact to decide the use of SNS (De Rossi, 2007;Sharif and Sargent, 2006;Binsahl and Chang 2012), few examinations have investigated the impacts of SNS to nursing instruction in Saudi Arabia devoted to ponder behaviour for nursing student in the computerized age. Accessible written works have demonstrated that SNS could represent the deciding moment on the investigation achievement of the student, such as Facebook and different SNS speak to the greatest diversion to undergrads in this manner influencing their examination behaviour and grades; De Rossi (2007) who said long range interpersonal communication is a critical viewpoint among the present youths and postures adequacy if appropriately diverted; the investigation of Ito et al (2008), who guaranteed that the computerized world or long range informal communication is making new open doors for the adolescent to think about social standards, investigate premiums, create specialized abilities, and explore different avenues regarding new types of self-articulation, and some more.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicates that youngsters ought to spend an average of no greater than 1 to two hours in line with day watching television. Sharif and Sargent (2006) expressed in their exploration that substance and screen time independently affects scholarly execution. In this investigation, both screen time and media content is viewed as a factor that can be related with TV, motion picture, and computer game presentation to scholarly execution.…”
Section: Introductionmentioning
confidence: 99%